SISTEM PENDUKUNG KEPUTUSAN PENGADAAN BAHAN PUSTAKA PERPUSTAKAAN STT ADISUTJIPTO MENGGUNAKAN METODE TOPSIS - Honggowibowo, Anton Setiawan (SENATIK STT Adisutjipto, 2016)
Library STT Adisutjipto still use manual for procurement of library materials. So that the workers have to put together a list of books needs of various departments request then selects request books one by one so often is not appropriate in the procurement process. To overcome these problems will be built a decision support system that can provide an alternative solution in the procurement process book. By using TOPSIS librarian can take a few titles that have the greatest value of any calculation, so that will be obtained several lists of books that will be held. TOPSIS method aims to select an alternate book based on criteria (budget, proposals, books are often borrowed, price, edition of the book, stock, date of publication and publisher) which has been determined. The calculation process is done by finding the weight value of each alternative on each criterion. The selected book is the greatest value as the best alternative. The final result of the calculation method TOPSIS with manual calculation is the same, where the book Ansi (BK06) is a book that has the greatest value. The value for each method is BK06 with a value of 0.7781 on TOPSIS and BK06 to the value of 0.7781 on manual calculations.